COHERENT RISK MEASUREMENT - Valentino Budhidarma (Universitas Pelita Harapan, 2022)
In the world of finance, risk management refers to the practice of identifying potential risks in advance, analyzing them, and taking precautionary steps to reduce/curb the risk. When an entity makes an investment decision, it is exposed to many financial risks. The purpose of this paper is to test whether any of the five risk measurements: (1) alpha, (2) beta, (3) standard deviation, (4) Sharpe ratio, and (5) Treynor Ratio are coherent. The results show that none of the five risk measurements are coherent.